PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF GAMIFIKASI “GEMA” UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA DI KELAS V - Sudrajat; Aura Maulida Rachma; Nindy Mardani (JURNAL FIRNAS, 2025)
In response to the rapid advancements in education, teachers face the challenge of designing engaging and meaningful learning experiences. Mathematics, often perceived as a difficult subject due to its computational nature, remains a particular area of concern. Preliminary observations indicate that elementary mathematics instruction frequently relies on conventional methods, lacking innovative approaches, which results in low student engagement and participation. This study aims to enhance mathematics learning outcomes on the topic of plane figure perimeter among fifth-grade students at SDN 3 Sumber by implementing “GEMA", a gamification-based interactive learning medium. The research involved 23 students (11 female, 12 male) and employed Classroom Action Research (CAR) conducted in three phases: pre-cycle, Cycle I, and Cycle II. The pre-cycle stage included a diagnostic assessment to evaluate students' baseline abilities. Cycle I utilized the Discovery Learning model, while Cycle II incorporated Problem-Based Learning (PBL) alongside the "GEMA" interactive media. Findings revealed a significant improvement, with an 87% completion rate (20 students meeting passing criteria) in Cycle II. The study concludes that gamification-based interactive media effectively enhances mathematics learning outcomes in plane figure perimeter.